PEMANFAATAN KEANEKARAGAMAN HAYATI LOKAL SEBAGAI SUMBER PENDAPATAN MASYARAKAT PESISIR PANGANDARAN - Sobarna, Cece; Amien, Suseno; Afsari, Asri Soraya (Universitas Padjadjaran, 2024)
The Dahon plant (Nypa Rruticans) is a multipurpose plant whose existence has begun to be threatened today along with the rapid development of tourist destinations in Pangandaran. The lack of development of dahon sugar craftsmen in Pangandaran considering that the process of making dahon sugar requires special skills and perseverance whereas community resources in Parapat Hamlet are quite potent. This community service program aims to provide skills to process dahon plants into sugar for prospective groups of dahon craftsmen regularly. Service activities are carried out through counseling techniques and direct practice. The counseling carried out was in the form of providing motivational materials and counseling on post-harvest cultivation and nipah processing, as well as the practice of making dahon sugar. After counseling and practice of making dahon sugar to the target partners of the Berkah Nipah Self-Help Group, it appears that there are positive and encouraging developments for the target partners, as follows: (1) the target partners get additional insight and knowledge about the functions and benefits of the nipah plant scientifically, ( 2) target partners get new experience in the practice of making dahon sugar, (3) target partners are optimistic and enthusiastic to continue making dahon sugar in Parapat Hamlet, Pangandaran, and (4) knowledge and abilities of Mr. Sarli as an instructor can finally be lowered to young people. Through the results of this service activity, it is hoped that new dahon craftsmen will emerge and the ongoing development of the younger generation an ongoing basis.ABSTRAK Tanaman Dahon (Nypa Rruticans) merupakan tanaman serba guna yang keberadaannya mulai terancam saat ini seiring dengan pesatnya perkembangan destinasi wisata di Pangandaran. Kurangnya pengembangan pengrajin gula dahon di Pangandaran mengingat proses pembuatan gula dahon memerlukan keterampilan dan ketekunan khusus padahal sumber daya masyarakat di Dusun Parapat cukup potensial. Program pengabdian masyarakat ini bertujuan untuk memberikan keterampilan mengolah tanaman dahon menjadi gula bagi calon kelompok pengrajin dahon secara rutin. Kegiatan pengabdian dilakukan melalui teknik penyuluhan dan praktek langsung. Penyuluhan yang dilakukan berupa pemberian materi motivasi dan penyuluhan budidaya pasca panen dan pengolahan nipah, serta praktik pembuatan gula dahon. Setelah dilakukan penyuluhan dan praktek pembuatan gula dahon kepada mitra binaan Kelompok Swadaya Berkah Nipah, terlihat adanya perkembangan yang positif dan menggembirakan bagi mitra binaan, sebagai berikut: (1) mitra binaan mendapatkan tambahan wawasan dan pengetahuan tentang fungsi dan manfaat tanaman nipah secara ilmiah, (2) mitra binaan mendapatkan pengalaman baru dalam praktek pembuatan gula dahon, (3) mitra binaan optimis dan antusias untuk terus membuat gula dahon di Dusun Parapat, Pangandaran, dan (4) ilmu dan kemampuan Pak Sarli sebagai instruktur akhirnya bisa diturunkan ke generasi muda. Melalui hasil kegiatan pengabdian ini diharapkan akan muncul pengrajin-pengrajin dahon baru dan pembinaan generasi muda secara berkesinambungan.